Development of quality of nursing care in Thailand - Kunaviktikul W. (2014)
Background. In Thailand there is a need to establish definitions of quality of nursing care and to determine how it is measured. There is an urgent need to focus more closely on indicators of nursing quality. In Thailand there is no agreed upon definition of quality nursing care or indicators by which to measure it. Purpose. The purpose of this research was to develop a definition of quality of nursing care and to begin the process of defining quality of care indicator measures to evaluate the care given in acute care settings. Methods. This descriptive study was conducted in Thailand. The process included two phases. The first phase used individual interviews and focus group discussion and the second phase included consultation with quality of nursing care experts. An interview guide was used to structure the interviews and the draft definitions of quality and suggested indicators were used when consulting with the experts in the second phase of the study. Findings. The findings are organized into two sections: (1) definition of quality of nursing care and quality of nursing indicators; and (2) consultation with Thailand quality experts to refine the definition and quality of care indicators. The indicators were categorized into three groups: structure, process, and outcome. Limitations. This descriptive study using qualitative method relied upon the opinions of various stakeholders. Their opinions may or may not have any direct relationship to the scientific literature related to quality. Many of the indicators need to be further refined. Conclusions. The findings generally support the initial work done in the United States of America. There is a need to further refine the various Thailand indicators. This study is the first in Thailand that has attempted to address quality of nursing care.